2022
DOI: 10.1109/tuffc.2022.3220082
|View full text |Cite
|
Sign up to set email alerts
|

Miniature Ferroelectret Microphone Design and Performance Evaluation Using Laser Excitation

Abstract: Miniature microphones suitable for measurements of ultrasonic wave field scans in air are expensive, or lack sensitivity or do not cover the range beyond 100 kHz. Essential, that they are too large for such fields measurements. The use of ferroelectret (FE) film is proposed to construct a miniature, needle-style 0.5 mm diameter sensitive element ultrasonic microphone. FE has an acoustic impedance much closer to that of air compared to other alternatives, and is low cost and easy to process. Performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Moreover, studies have been conducted on acoustic sensing in the ultrasound field. Svilainis et al [87] reported on the design and performance evaluation of a miniaturized air-coupled ultrasonic microphone made of FENG film. The construction of the microphone (left) and the assembled device (right) are shown in Figure 5e.…”
Section: Acoustic Sensingmentioning
confidence: 99%
“…Moreover, studies have been conducted on acoustic sensing in the ultrasound field. Svilainis et al [87] reported on the design and performance evaluation of a miniaturized air-coupled ultrasonic microphone made of FENG film. The construction of the microphone (left) and the assembled device (right) are shown in Figure 5e.…”
Section: Acoustic Sensingmentioning
confidence: 99%